Synthesis of new organic semiconductors based on poly(2-anilinoethanol) doped with different acids and investigation of their electro-optical properties - Ahlatcioglu, E.; Senkal, B. F.; Yakuphanoglu, F.; Mansour, Sh. A. (WILEY, 2013)
The polyaniline (PANI) was synthesized using different dopant acids (iminodiacetic, methanesulfonic, phosphoric, and boron trifuoride) using oxidative polymerization method. These obtained new polymers were characterized by using spectrophotometric methods such as FTIR, UVvis. The calculated value of the optical energy gap for the doped investigated polymer was reached to 3.70 eV for PANI-OH doped by boron trifuoride. The conductivity of the polymers was also investigated. The direct current (dc) conductivity as a function of temperature for the doped polymers has been studied. The results show increase in the conductivity with increase in temperature. Also, the value of dc conductivity at room temperature was found to be greater than that of the undoped PANI by nearly one to four orders of magnitude with respect to the used dopant acid. POLYM. ENG. SCI., 2013. (c) 2012 Society of Plastics Engineers
Keywords: RING-SUBSTITUTED POLYANILINE; CONDUCTING POLYANILINE; PHYSICAL-PROPERTIES; OPTICAL-PROPERTIES; ANILINE; POLYMERIZATION; COPOLYMER; FABRICATION; COMPOSITES; SOLUBILITY; Engineering; Polymer Science